Implementation of the Role of the Marriage Guidance and Preservation Advisory Board (BP4) in Maintaining Household Harmony - Ayi Ishak Sholih Muchtar; Ah. Fathonih; Aden Rosadi; Januri Januri (International Journal of Law and Society, 2025)
This research addresses the high divorce rate in three districts and cities, highlighting the lack of household harmony and integrity. The study focuses on the role and function of the Marriage Guidance and Preservation Advisory Board (BP4) in consultation and mediation. The objectives of the research are: 1) To identify the role of BP4 in fostering household harmony, 2) To examine the implications of Family Law in BP4’s role, and 3) To analyze BP4’s contribution to household harmony in East Priangan. The research employs a sociological juridical approach, examining the law based on norms and regulations while assessing its empirical application in community life. The research adopts qualitative methods. The findings show that: 1) BP4's role in maintaining household harmony is functioning normatively and functionally through non-litigation counseling and mediation, but its implementation remains uneven and reactive, preventing optimal development of the preventive function. 2) BP4’s legal implications are strong as a pre-litigation mechanism, but its limited authority and minimal integration with the judicial system hinder its effectiveness. 3) Barriers to BP4’s assistance include low participation, limited legal authority, a litigative culture, and weak institutional capacity. The research suggests a new model for Restorative-Preventive Family Governance to strengthen BP4’s role in conflict prevention